2020
DOI: 10.3390/antiox9111053
|View full text |Cite
|
Sign up to set email alerts
|

The Modulatory Role of Vitamin C in Boldenone Undecylenate Induced Testicular Oxidative Damage and Androgen Receptor Dysregulation in Adult Male Rats

Abstract: Background: This study explored the effect of vitamin C (Vit-C) administration on the reproductive function of adult male Wistar rats injected with boldenone undecylenate (BOL). Methods: Rats were randomly assigned into control, vehicle control, Vit-C (120 mg/kg b.wt./day, orally), BOL (received 5 mg/kg b.wt./week, IM) and BOL+Vit-C-treated groups. After eight weeks, hormonal assay, semen evaluation, testicular enzymes, and antioxidants biomarkers were assessed. Besides, the histopathological and immunohistoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 63 publications
3
26
0
Order By: Relevance
“…The activation of the ARs in liver cells may increase ROS leading to hepatic cell degeneration which eventually leads to clinical signs of hepatotoxicity (Solimini et al, 2017). The impact of BLD on AR expressions in rat testes was previously reported by our earlier study (Behairy et al, 2020b). The current findings are similar to Patanè et al (2020), who hypothesized that oxidative stress in hepatic cells had been associated with hepatotoxicity caused by AASs.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The activation of the ARs in liver cells may increase ROS leading to hepatic cell degeneration which eventually leads to clinical signs of hepatotoxicity (Solimini et al, 2017). The impact of BLD on AR expressions in rat testes was previously reported by our earlier study (Behairy et al, 2020b). The current findings are similar to Patanè et al (2020), who hypothesized that oxidative stress in hepatic cells had been associated with hepatotoxicity caused by AASs.…”
Section: Discussionsupporting
confidence: 91%
“…The 17-beta-hydroxy group of injectable AASs, like BLD, is esterified, yielding more lipid-soluble products slowly released into the blood ( Liddle and Connor, 2013 ). Several health disorders have been associated with BLD misuse like renal damage ( Barakat et al, 2015 ), cardiovascular disorders ( Tousson et al, 2016 ), liver dysfunction ( Ziaolhagh et al, 2018 ), and testicular problems ( Behairy et al, 2020b ).…”
Section: Introductionmentioning
confidence: 99%
“…Five microns thick tissue were prepared, stained with haematoxylin and eosin stains (Slaoui & Fiette, 2011), mounted in Canada Balsam, and examined by light microscope recording any histological change. A quantitative lesion scoring and morphometric assessment following (Behairy et al., 2020). All measurements were performed using AmScope software ToupView, AmScope, USA, and the results were shown in percentages (means ± SE ).…”
Section: Methodsmentioning
confidence: 99%
“…Our results also revealed that intraperitoneal injection of boldenone (5 mg/kg) induced oxidative stress in testicular tissue which was indicated by signi cant increase in MDA and NO and on the other hand a signi cant lowering of GSH and SOD in testiculat tissue. In a previous study (Behairy et al, 2020), authors veri ed an elevation of MDA and No as well as a decreament of SOD and GSH in rabbits due to injection with boldenone. Furthermore, a signi cant induction of lipid peroxidation, as well as complete inhibition of antioxidant capacity in testicular tissues in rats (S. S. Ibrahim & Said, 2019).…”
Section: Discussionmentioning
confidence: 87%